FORMATION OF NUTRITIONAL BEHAVIOR OF ENGINEERING AND TECHNICAL WORKERS OF COAL ENTERPRISES - Наталья Васильевна Тапешкина; Наталья Сергеевна Алексеева; Ольга Николаевна Блажина; Анастасия Валерьевна Ямщикова; Татьяна Георгиевна Корсакова (Медицина в Кузбассе, 2024)
Introduction. Nutrition is one of the important environmental factors that determine human health. Improper nutritional behavior is the leading cause of poor health and the development of diet-dependent diseases.